The Effect of Self Efficacy, Organizational Culture, Knowledge Sharing on Organizational Citizenship Behavior (OCB) Through Work Motivation - Aulia Rosalinda Baladika Jayanti; Dewi Susita; Corry Yohana; Sonny Taufan (International Journal Labs, 2026)
This study examined the lack of Organizational Citizenship Behavior (OCB) among Functional Officials for Industrial Development (PFPI) at the Industrial Services Standardization and Policy Agency (Badan Standardisasi dan Kebijakan Jasa Industri [BSKJI]), Ministry of Industry, which currently hinders the achievement of national industrial development objectives. The purpose of this study was to investigate the direct and indirect effects of self-efficacy, organizational culture, and knowledge sharing on OCB, with work motivation as a mediating variable. Data were collected from 205 randomly selected PFPI officials through questionnaires and analyzed using Structural Equation Modeling (SEM) with AMOS through a quantitative explanatory research approach. The results showed that self-efficacy, organizational culture, and knowledge sharing significantly improved OCB, both directly and indirectly. Work motivation partially mediated all examined relationships. Work motivation emerged as the strongest direct predictor of OCB, while organizational culture was the primary factor influencing work motivation and demonstrated the greatest cumulative effect on OCB. This study concludes that a holistic approach is required to enhance OCB. The findings imply that management should prioritize the development of a supportive organizational culture and the establishment of structured knowledge-sharing platforms to strengthen work motivation, thereby encouraging voluntary extra-role behaviors that contribute to institutional success.